Impoliteness Strategies in Family Interaction in The D’Amelio Show Season 3 - Desiana Salsabila; Irman Nurhapitudin; Ice Sariyati (Linguistics and ELT Journal, 2026)
This study aims to examine the types and functions of impoliteness strategies used by D’Amelio family in The D’Amelio Show Season 3. This research used a qualitative-descriptive method to provide an in-depth analysis. The data were selected using purposive sampling of 10 episodes from season 3 of The D’Amelio Show.  The data were transcribed verbatim and analyzed using Culpeper’s framework (1996; 2011). The results analyzed 22 utterances to five impoliteness strategies: bald on record, positive, negative, sarcasm/mock politeness, and withhold politeness. Negative impoliteness was found to be the most frequently used impoliteness strategy (40.91%), while bald on record impoliteness and withhold politeness were the least frequent (4.55%). In terms of function, three functions were examined: affective, coercive, and entertaining. It was found that the affective function was widely used (50.0%).  The use of impoliteness reflects social dynamics within families, suggesting that impoliteness is not merely a verbal attack but also a means of expressing emotions, displays of intimacy, and interpersonal conflict. This also depends heavily on the context and the relationship between speakers. These findings contribute to a deeper understanding of impoliteness in mediated interpersonal communication and provide insights for further research in similar contexts.